Ethics For Nurses : Theory and Practice. - Cranmer, Pam (McGraw-Hill Education, 2013)
This book on ethics for nurses will guide students and nurses through the process of recognizing ethical dilemmas in nursing practice, and better prepare them to nurse in an ethical way.